1964
DOI: 10.1037/h0042377
|View full text |Cite
|
Sign up to set email alerts
|

Motivational properties of hypothalamic aggression in cats.

Abstract: Hypothalamic stimulation caused 9 normally nonaggressive cats to make predatory attacks on rats. During stimulation, all learned a Y maze to obtain a rat that they could attack. When stimulation was omitted, performance of the learned habit deteriorated and there were no attacks. When the stimulation was turned on during eating of cat food, the cats switched to attack on a nearby rat, indicating that the attack was not due to hunger. It was concluded that the performance of the attack was rewarding, and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…If the target is defenseless, death can result (cf. Roberts and Kiess, 1964). Conversely, if the target is capable of effective counter-aggression, attack gives way to "aggressive" postures, threats, etc.…”
Section: Discussionmentioning
confidence: 99%
“…If the target is defenseless, death can result (cf. Roberts and Kiess, 1964). Conversely, if the target is capable of effective counter-aggression, attack gives way to "aggressive" postures, threats, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in the expression of aggression might be related with several behavioral or adaptive characteristics. In support of the aforementioned, it has been shown that dominance might be based on individual skills during competition and not necessarily the age hierarchy within the social group [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mice reveal that grouping adult male mice in cages can result in increased aggression, and could as well reflect a pattern in the social order of dominance [2][3][4][5][6][7][8][9][10][11][12][13]. When a group of monkeys of different sizes were merged and the social order of dominance was observed, some small animals were aggressive and constantly challenged the authority of bigger animals in the social structure, while some were placid and did not challenge the bigger animals [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus-bound attack, however, has been studied extensively in the cat. It has been divided behaviorally into affective attack and staIking attack (Wasman & Flynn, 1962) for which the more general motivational correlates are escape (Adams & Flynn, 1966) and approach (Roberts & Kiess, 1964), respectively. The present re port describes the preliminary results of stimulusbehavior a live mouse, a dead mouse, two wedges of wood, and several food pellets were paced in the box du ring screening.…”
Section: Discussionmentioning
confidence: 99%